Production of Bacterial Cellulose from Coffee Waste Extract Enriched with Carbon Source of Molasses and Pineapple Peel Waste: Production of Bacterial Cellulose from Coffee Waste Extract - Mora, Giral Baines; Permatasari, Dewi; Wahyudi, Aleyda; Ardyati , Tri (Journal of Tropical Life Science, 2026)
Coffee waste is an agricultural by-product that has been commonly used as compost and animal feed. It contains complex carbohydrate sources that can be further utilized for the production of bacterial cellulose. However, the sugar content in coffee waste is limited, so additional sugar sources such as molasses and pineapple peel extract are needed. Molasses and pineapple peel extract serve as substitutes for glucose and are expected to optimize the production of bacterial cellulose. This study aimed to determine the effect of different concentrations of molasses (0.5%, 2.5%, and 5% v/v) and pineapple peel extract (20% and 40% v/v) in coffee waste extract medium on bacterial cellulose production and to characterize the resulting membranes. The research stages included: (1) enrichment of starter culture and standardization of bacterial cell density; (2) extraction of coffee waste and pineapple peel; (3) production of bacterial cellulose using coffee waste extract medium supplemented with molasses or pineapple peel extract at varying concentrations; (4) physicochemical characterization of bacterial cellulose including weight, thickness, surface area, pH change, and tensile strength; and (5) analysis of membrane surface structure using SEM. The best physicochemical characteristics were obtained from the medium supplemented with 5% molasses and 20% pineapple peel extract. These treatments also yielded the best results in terms of SEM analysis and tensile strength.